2022
DOI: 10.3389/fmolb.2022.964295
|View full text |Cite
|
Sign up to set email alerts
|

Drug affinity-responsive target stability unveils filamins as biological targets for artemetin, an anti-cancer flavonoid

Abstract: Artemetin is a valuable 5-hydroxy-3,6,7,3′,4′-pentamethoxyflavone present in many different medicinal plants with very good oral bioavailability and drug-likeness values, owing to numerous bioactivities, such as anti-inflammatory and anti-cancer ones. Here, a multi-disciplinary plan has been settled and applied for identifying the artemetin target(s) to inspect its mechanism of action, based on drug affinity-responsive target stability and targeted limited proteolysis. Both approaches point to the disclosure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Published on 12 June 2024 as DOI 10.1124/pharmrev.123.001028 This article at ASPET Journals on June 27, 2024 pharmrev.aspetjournals.org Downloaded from proteins; on the other hand, the positive results of some low-abundance proteins can easily be overlooked in SDS-PAGE analysis; moreover, incorrect manipulation may also lead to false-positive results. Therefore, DARTS is usually not used alone but rather in combination with other techniques such as liquid chromatography/tandem mass spectrometry (LC-MS/MS) (Ferraro et al, 2022;Park et al, 2024), coimmunoprecipitation (Co-IP) (Wang et al, 2021), and cellular thermal transfer assay (CETSA) (Wu et al, 2021), to validate and identify potential drug targets. In addition, some studies, such as functional assays and in vivo experiments, are required to confirm the relevance of the targets.…”
Section: A Drug Affinity Responsive Target Stability (Darts)mentioning
confidence: 99%
“…Published on 12 June 2024 as DOI 10.1124/pharmrev.123.001028 This article at ASPET Journals on June 27, 2024 pharmrev.aspetjournals.org Downloaded from proteins; on the other hand, the positive results of some low-abundance proteins can easily be overlooked in SDS-PAGE analysis; moreover, incorrect manipulation may also lead to false-positive results. Therefore, DARTS is usually not used alone but rather in combination with other techniques such as liquid chromatography/tandem mass spectrometry (LC-MS/MS) (Ferraro et al, 2022;Park et al, 2024), coimmunoprecipitation (Co-IP) (Wang et al, 2021), and cellular thermal transfer assay (CETSA) (Wu et al, 2021), to validate and identify potential drug targets. In addition, some studies, such as functional assays and in vivo experiments, are required to confirm the relevance of the targets.…”
Section: A Drug Affinity Responsive Target Stability (Darts)mentioning
confidence: 99%
“…For the interacted 480 nodes, the number of edges was 8738. For all the nodes of the PPI net- Anti-cancer effects [28,29]…”
Section: Construction Of Ppi Networkmentioning
confidence: 99%
“…Pharmacological research has shown that it has anti-virus, anti-bacteria, anti-oxidative, anti-inflammatory, anti-dermatitis, gastro-protective, and anti-cancer effects, mainly due to the presence of essential oils, flavonoids, and organic acids [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Pharmacological research has identified various anti-cancer components of Aiye, including jaceosidin, irigenin, luteolin, eriodictyol, apigenin, eupatilin, casticin, and artemetin [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In obesity, the secretion of adipokines by adipose tissue was dysregulated, characterized by the up-regulation of proinflammation adipokines and the down-regulation of anti-inflammation adipokines [ 30 ].…”
Section: Introductionmentioning
confidence: 99%